On the complexity of the ideal of absolute null sets - Zakrzewski, P. (Український математичний журнал, 2012)
Answering a question posed by Banakh and Lyaskovska, we prove that, for an arbitrary countable infinite amenable group G, the ideal of sets having μ-measure zero for every Banach measure μ on G is an Fσδ subset of {0; 1}G. У вiдповiдь на питання, поставлене Банахом i Ляскiвською, доведено, що для будь-якої злiченної аменабельної групи G iдеал множин, що мають нульову μ-мiру для будь-якої мiри Банаха μ на G, є Fσδ-пiдмножиною {0,1}G.